Orbital volume augmentation using expandable hydrogel implants in acquired anophthalmia and phthisis bulbi. (3rd March 2016) - Kim, Esther Lee; Bernardino, Carlo Rob; Levin, Flora
ABSTRACT: The purpose of this study is to describe our experience using expandable spherical hydrogel implants and injectable hydrogel pellets for orbital volume augmentation in cases of post-enucleation socket syndrome after acquired anophthalmia or phthisis bulbi. We retrospectively reviewed the clinical records of all adult patients who received an expandable hydrogel implant for orbital volume loss following enucleation or phthisis bulbi at the Emory Eye Center between 2004 and January 2007 and the Yale Eye Center between 2009 and 2011. The study included 9 women and 5 men with a mean age of 51.2 years old (range 35-76 years old). Follow-up spanned 6 to 71 months (median of 18.5 months). Four patients received spherical hydrogel implants and 10 patients received hydrogel pellet injections. On average, nine pellets (range 5-16) were placed in each patient over an average of 1.7 injections (range 1-3). Most commonly, five pellets were injected per session, as was the case for 13 of the 17 treatment sessions. Post-operative complications included 2 cases of pellet migration, one subcutaneously and one anteriorly due to insufficiently posterior implant placement, and 1 hospital admission for pain after injection of 10 pellets in one visit. All patients experienced an overall subjective improvement in cosmesis. Self-expandable hydrogel implants appear to offer several advantages over other existing options for orbital volume augmentation, as they are easy to place, generally well-tolerated, volume-titratable, and to the extent that our follow-up shows, may be a safe and durable means of treating orbital volume loss in patients with acquired anophthalmia and phthisis bulbi.